Replotting marriage in nineteenth-century British literature - Galvan, Jill Nicole, 1971-; Michie, Elsie B. (Elsie Browning), 1948- (The Ohio State University Press, 2018)
"This volume puts marriage in conversation with many aspects of culture--education, anthropology, Darwinism, crime, and more--widening the repertoire of questions scholars ask about fictional coupling. Attending closely to genre and narrative, it analyzes the marriage story as formally diverse rather than a familiar plot line"-- Provided by publisher
Keywords: Marriage in literature.; English fiction -- 19th century -- History and criticism.; English literature -- 19th century -- History and criticism.; Mariage dans la littérature.; Roman anglais -- 19e siècle -- Histoire et critique.; Littérature anglaise -- 19e siècle -- Histoire et critique.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; LITERARY COLLECTIONS -- General.; English fiction; English literature; Marriage in literature; 1800-1899; Criticism, interpretation, etc.; Electronic books.